Hubungan Tingkat Kecemasan Terhadap Sikap Remaja Akibat Pandemik Covid-19 - Devra Jovana Clarissa Suryaatmaja; Imanuel Sri Mei Wulandari (Universitas Malahayati Lampung, 2020)
ABSTRACT: CORRELATION BETWEEN STATE OF ANXIETY AND ADOLESCENT ATTITUDE DUE TO COVID-19 Background: The current pandemic shaking the world is Coronavirus Disease 19 or commonly abbreviated as COVID-19. This disease attacks human respiratory system and can cause death. As a result of this pandemic, anxiety arises from all communities, including adolescents. Educational facilities are temporarily closed. Therefore, the learning method uses an online system. One of the factors that cause anxiety from teenagers is fear because they do not know whether the people around them are healthy or not, so they also avoid crowd or gathering which can invite large number of people. Moreover, they fear about themselves whether they are bringing the virus to those around them. Some of them are also afraid of fake news about COVID-19 which are scattered around carelessly on social media.Purpose: The purpose of this study is to determine the correlation between the anxiety level and adolescent attitudes in dealing with COVID-19.Methods: The researcher uses quantitative analytical correlation methods, with a cross-section approach. The population in this study are all from high school students of Salemba Adventist School not less than 138 people and the total of samples in this study are 51 students.Results: The results of this study show that the level of anxiety is at a moderate level (64.7%) and indicate very positive attitude (52.9%) of the respondents in responding to the COVID-19 pandemic. The bivariate analysis found that there is a significant relationship between the level of student anxiety and student attitudes with a value of p 0.05.Conclusion: It can be concluded that teenagers want to follow health protocols to keep themselves healthy and avoid this disease by maintaining personal hygiene such as wash their hands periodically and consume nutritious foods and drink vitamins. Key Word: Anxiety, attitude, Covid-19 INTI SARI: HUBUNGAN TINGKAT KECEMASAN TERHADAP SIKAP REMAJAAKIBAT PANDEMIK COVID-19 Latar Belakang: Pandemik saat ini yang sedang mengguncang dunia adalah Coronavirus Disease 19 atau biasa disingkat COVID-19. Penyakit ini menyerang sistem pernapasan manusia dan bisa menyebabkan kematian. Akibat pandemik ini, maka timbul kecemasan dari semua masyarakat termasuk anak remaja. Sarana pendidikan ditutup sementara sehingga metode pembelajaran pun menggunakan sistem online. Salah satu faktor timbulnya kecemasan dari remaja adalah karena takut karena mereka tidak tahu apakah orang-orang di sekitar mereka sehat atau tidak sehingga mereka juga menghindari keramaian atau pertemuan yang mengundang banyak orang. Dan diri mereka sendiri pun takut apakah mereka membawa virus tersebut kepada orang-orang di sekitarnya. Beberapa juga takut akan adanya berita palsu mengenai COVID-19 yang suka beredar sembarangan.Tujuan: Tujuan penelitian ini adalah untuk mengetahui hubungan antara tingkat kecemasan dengan sikap remaja dalam menghadapi COVID-19.Metode: Peneliti menggunakan metode kuantitatif korelasi analitik, dengan pendekatan cross sectiona. Populasi pada penelitian ini adalah seluruh siswa SMA Advent Salemba sebanyak 138 orang dan yang menjadi sampel dalam penelitian ini sebanyak 51 siswa.Hasil: Hasil penelitian ini menunjukkan bahwa tingkat kecemasan berada pada tingkat kecemasan sedang (64,7%) dan sikap yang sangat baik (52,9%) dari responden dalam menyikapi pandemik COVID-19. Adapun Analisa bivariat didapati terdapat hubungan yang siginifikan antara tingkat kecemasan siswa dengan sikap siswa dengan nilai p 0.05. Kesimpulan: Dapat disimpulkan bahwa para remaja mau mengikuti protokol kesehatan untuk menjaga dirinya agar tetap sehat dan terhindar dari penyakit ini dengan menjaga kebersihan diri seperti mencuci tangan setiap waktu dan makan makanan yang bergizi serta minum vitamin. Kata Kunci: Covid-19, Kecemasan, Sikap Remaja